The Importance of Anthropometric Indices for Assessing the Physical Development and Physical Fitness of Young Athletes - Akbarova G.Kh (Zien Journals, 2022)
Many authors have convincingly proved that the anthropometric indicators of a woman affect the state of the placenta, therefore, already in the process of pregnancy it affects the developing fetus and, as a result, the health of the future person. It is shown that the indicators of physical development are associated with the peculiarities of metabolism, in particular, with lipid metabolism in blood cells [6,9;] and, thus, anthropometry indicators can serve as markers of the state the body as a whole
Keywords: indicators; anthropometry; pregnancy; fetus